2019
DOI: 10.1001/jamafacial.2018.1829
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Indocyanine Green Angiography to Identify Clinical Factors Associated With Perfusion of Paramedian Forehead Flaps During Nasal Reconstruction Surgery

Abstract: Identifying factors affecting forehead flap neovascularization during nasal reconstruction surgical procedures using quantitative dynamics of fluorescence from indocyanine green angiography may be associated with reduced vascular complications.OBJECTIVES To identify quantifiable forehead flap perfusion measures using indocyanine green angiography during nasal reconstruction procedures and to evaluate clinical factors associated with neovascularization. DESIGN, SETTING, AND PARTICIPANTS Retrospective cohort stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 35 publications
0
38
0
Order By: Relevance
“…Multiple near-infrared video camera systems have been used for ICG angiography in the head and neck region. The most popular are the SPY Elite system (NOVADAQ Technologies Inc.), 1,21 the IC View System (Pulsion Medical Systems), the PDE-Neo system (Hamamatsu Photonics), 22,23 IR800 (Carl Zeiss AG), and Flow800 (OPMI Pentero, Carl Zeiss AG). 24 Some systems used filtered endoscope-integrated systems such as red/near-infrared excitation (filtered Xenon Short Arc lamp, Karl Storz) coupled to an infrared-sensitive threechip CCD camera (Karl Storz).…”
Section: Icg Angiography Software Systemsmentioning
confidence: 99%
See 3 more Smart Citations
“…Multiple near-infrared video camera systems have been used for ICG angiography in the head and neck region. The most popular are the SPY Elite system (NOVADAQ Technologies Inc.), 1,21 the IC View System (Pulsion Medical Systems), the PDE-Neo system (Hamamatsu Photonics), 22,23 IR800 (Carl Zeiss AG), and Flow800 (OPMI Pentero, Carl Zeiss AG). 24 Some systems used filtered endoscope-integrated systems such as red/near-infrared excitation (filtered Xenon Short Arc lamp, Karl Storz) coupled to an infrared-sensitive threechip CCD camera (Karl Storz).…”
Section: Icg Angiography Software Systemsmentioning
confidence: 99%
“…These tools may be helpful in qualitative or quantitative assessments. 1,25 Qualitative tools evaluate the generated fluorescence to evaluate the success of the inset of pedicled flaps or the anastomosis patency in free flaps. This provides a dynamic map of the dermal circulation that serves as a topographic analysis of the effective perfusion to the flap tissue, as shown in ►Fig.…”
Section: Perfusion Assessment Toolsmentioning
confidence: 99%
See 2 more Smart Citations
“…Surgeons considering a shift to a paradigm of an earlier flap division may benefit from quantifying flap neovascularization. In a 2019 retrospective review of 71 patients, Abdelwahab et al reported that the indocyanine green angiography (SPY Elite System; LifeCell [Branchburg NJ], Novadaq Technologies [Mississauga, ON, Canada) can effectively qualify and quantify perfusion. The system's infrared‐sensitive camera can measure the perfusion of the intravascular fluorescent dye, and ensure adequate perfusion of forehead flaps among high‐risk patients.…”
Section: Literature Reviewmentioning
confidence: 99%